Lipoprotein particle distribution and skeletal muscle lipoprotein lipase activity after acute exercise - Harrison, Michael (BioMed Central, 2012)
BACKGROUND: Many of the metabolic effects of exercise are due to the most recent exercise session. With recent advances in nuclear magnetic resonance spectroscopy (NMRS), it is possible to gain insight about which lipoprotein particles are responsible for mediating exercise effects. METHODS: Using a randomized cross-over design, very low density lipoprotein (VLDL) responses were evaluated in eight men on the morning after i) an inactive control trial (CON), ii) exercising vigorously on the prior evening for 100 min followed by fasting overnight to maintain an energy and carbohydrate deficit (EX-DEF), and iii) after the same exercise session followed by carbohydrate intake to restore muscle glycogen and carbohydrate balance (EX-BAL). RESULTS: The intermediate, low and high density lipoprotein particle concentrations did not differ between trials. Fasting triglyceride (TG) determined biochemically, and mean VLDL size were lower in EX-DEF but not in EX-BAL compared to CON, primarily due to a reduction in VLDL-TG in the 70–120 nm (large) particle range. In contrast, VLDL-TG was lower in both EX-DEF and EX-BAL compared to CON in the 43–55 nm (medium) particle range. VLDL-TG in smaller particles (29–43 nm) was unaffected by exercise. Because the majority of VLDL particles were in this smallest size range and resistant to change, total VLDL particle concentration was not different between any of these conditions. Skeletal muscle lipoprotein lipase (LPL) activity was also not different across these 3 trials. However, in CON only, the inter-individual differences in LPL activity were inversely correlated with fasting TG, VLDL-TG, total, large and small VLDL particle concentration and VLDL size, indicating a regulatory role for LPL in the non-exercised state. CONCLUSIONS: These findings reveal a high level of differential regulation between different sized triglyceride-rich lipoproteins following exercise and feeding, in the absence of changes in LPL activity.